Optimization of synthetic jet actuation by analytical modeling. Issue 4 (13th May 2021) - Huber, Max; Zienert, Andreas; Weigel, Perez; Schüller, Martin; Berger, Hans-Reinhard; Schuster, Jörg; Otto, Thomas
Abstract : Purpose: The purpose of this paper is to analyze and optimize synthetic jet actuators (SJAs) by means of a literature-known one-dimensional analytical model. Design/methodology/approach: The model was fit to a wide range of experimental data from in-house built SJAs with different dimensions. A comprehensive parameter study was performed to identify coupling between parameters of the model and to find optimal dimensions of SJAs. Findings: The coupling of two important parameters, the diaphragm resonance frequency and the cavity volume, can be described by a power law. Optimal orifice length and diameter can be calculated from cavity height in good agreement with literature. A transient oscillation correction is required to get correct simulation outcomes. Originality/value: Based on these findings, SJA devices can be optimized for maximum jet velocity and, therefore, high performance.